Making Waves: Circumventing Domestic Law on the High Seas - Wolf, Shannon Renton (2003)
As abortion is illegal in Ireland, many Irish women who seek to exercise reproductive rights cross the Irish Sea to have abortions in England. However, given the cost of such travel, some Irish women do not have access to abortion. A Dutch organization, Women on Waves, recently attempted to sail a Dutch-registered ship to countries where abortion is either illegal or difficult to obtain. To circumvent domestic law, the abortions would be performed in international waters. While the effort was unsuccessful, the attempt raises a host of issues involving international law, state sovereignty, the law of the sea, and human rights. This Note considers whether and when Ireland has legal authority to assert jurisdiction over the Dutch abortion ship